Geometrical coupling fields of a hypercomplex type - Marão, José Antônio Pires Ferreira; Borges Neto, Manoel Ferreira [UNESP] (Academic Publications, 2013)
This paper presents an application of Laplace's equation obtained from a quaternionic function that satisfies the Cauchy-Riemann conditions determined earlier by Borges and Machado [#!BorgesZeMarcio!#]. Therefore, we show that it is possible to express in a single equation gravity, electric and magnetic potential fields, and this expression can only be provided due to a function that will be called here the coupling function.
Keywords: quaternions; Laplace's equations; geoemtrical coupling fields